2016
DOI: 10.18632/oncotarget.12354
|View full text |Cite
|
Sign up to set email alerts
|

A module of inflammatory cytokines defines resistance of colorectal cancer to EGFR inhibitors

Abstract: Epidermal Growth Factor Receptor (EGFR) activates a robust signalling network to which colon cancer tumours often become addicted. Cetuximab, one of the monoclonal antibodies targeting this pathway, is employed to treat patients with colorectal cancer. However, many patients are intrinsically refractory to this treatment, and those who respond develop secondary resistance along time. Mechanisms of cancer cell resistance include either acquisition of new mutations or non genomic activation of alternative signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 39 publications
4
41
1
Order By: Relevance
“…Consistently, patients with stable disease (SD) or an overall response (OR) to CTX therapy displayed lower IL-1R1 expression than the non-responding patients ( Figure 1 ). In line with our previous work [ 26 ], we conclude that increased expression of both IL-1 ligands (IL-1A and IL-1B) and receptor (IL-1R1) is associated with resistance to EGFR targeted therapy.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Consistently, patients with stable disease (SD) or an overall response (OR) to CTX therapy displayed lower IL-1R1 expression than the non-responding patients ( Figure 1 ). In line with our previous work [ 26 ], we conclude that increased expression of both IL-1 ligands (IL-1A and IL-1B) and receptor (IL-1R1) is associated with resistance to EGFR targeted therapy.…”
Section: Resultssupporting
confidence: 92%
“…Several clinical studies indicate that overexpression of inflammatory cytokines, such as IL-1, IL8, IL6 or CXCL1, correlates with cancer progression and decreased response to EGFR targeting therapy [ 25 , 27 ]. We previously reported that the abundance of IL-1 cytokines predicts sensitivity to EGFR blockage [ 26 ]. To further assess the clinical relevance of our results, we explored whether the receptor for IL-1, namely IL-1R1, was enriched in tumors from patients exhibiting attenuated response to anti-EGFR antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefits are the same for both wild-type and mutant KRAS tumors (234). It would be interesting to see the performance of combination cetuximab with CD73 inhibitors in preclinical CRC studies considering that inflammation is a mechanism of resistance to cetuximab (259). In melanoma, combination BRAF and MEK inhibitors with an A2AR antagonist induces significant tumor control in preclinical studies (41).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of this alternative pathway was postulated as an escape mechanism of erlotinib-resistant cells a view that was further supported by sensitization of these cells to erlotinib by tocilizumab mediated IL-6 receptor inhibition (50). Gelfo et al showed that activation of the EGFR in colorectal cancer cell lines mediated secretion of proinflammatory cytokines IL-1α, IL-1β and IL-8, which were associated with a cetuximab resistant phenotype in vitro ( 51 ) . Likewise, HER2 activation in breast cancer cell lines has been reported to induce secretion of proinflammatory cytokines IL-8 and CXCL1 (GRO) that were downregulated by gefitinib treatment, furthermore, circulating levels of IL-8 and CXCL1 in breast cancer patients highly correlated with HER2 expression (52).…”
Section: Egfr and Her2 Mediated Upregulation Of Oncogenic Cytokinesmentioning
confidence: 99%